Аналіз наукових поглядів на проблему формування емоційного інтелекту майбутнього вчителя музичного мистецтва - Ракітянська, Людмила (My University, 2019)
Мета дослідження: розкрити особливості професії «вчитель музичного мистецтва», що зумовлюють специфіку прояву його емоційного інтелекту та проаналізувати наукові погляди вчених на проблему його формування. У статті актуалізується проблема формування професійно значущих якостей майбутнього фахівця в контексті пріоритетних напрямів розвитку освіти. Надана коротка характеристика емоційного інтелекту як індивідуально-особистісного утворення, що забезпечує успішність в сфері професійної діяльності. Представлені різні наукові погляди щодо проблеми формування емоційного інтелекту вчителя музичного мистецтва. Встановлено, що специфіка прояву емоційного інтелекту вчителя зумовлена особливостями його професійної діяльності. Матеріал і методи дослідження. Логіка і методика наукового пошуку забезпечувались дотриманням вихідних теоретичних позицій, що утвердилися в науці, а також використанням теоретичних методів наукового пізнання: вивчення наукової літератури з проблеми дослідження, аналізу, синтезу, порівняння, узагальнення, цитування, що дозволило встановити характерні особливості уроку музичного мистецтва як основи для прояву емоційного інтелекту вчителя-музиканта та порівняти наукові погляди вчених на проблему його цілеспрямованого формування як професійно-значущої якості в контексті сучасних вимог. Проведений аналіз наукових поглядів на проблему формування емоційного інтелекту майбутнього вчителя музичного мистецтва дозволив узагальнити акцентовані вченими думки, щодо необхідності дослідження проблеми формування професійно значущих, особистісних якостей вчителя-музиканта, зокрема, його емоційного інтелекту, та виокремити його структурні складові. Результатом теоретичного рівня дослідження окресленої проблеми є визначені в узагальненому вигляді специфічні риси прояву емоційного інтелекту вчителя музичного мистецтва, зумовлені особливостями його професійно-педагогічної діяльності. Зроблено висновок про те, що специфіка прояву емоційного інтелекту вчителя-музиканта як складова його професіоналізму зумовлена, по-перше, гуманістичною сутністю педагогічної професії, а, по-друге, інтонаційно-звуковою природою музичного мистецтва, його емоційно-духовною домінантою. Емоційний інтелект вчителя музичного мистецтва конкретизований в таких поняттях як «переживання», «сенсорно-емоційно-інтелектуальне смислонародження», «образне мислення», «емоційна комунікація», «емпатійність», «самоконтроль», «саморегуляція». Отриманні знання сприятимуть розробці структурно-функціональної моделі формування емоційного інтелекту майбутнього вчителя-музиканта як його індивідуально-особистісної, професійно-значущої якості. The aim of the study. To reveal the features of the profession "teacher of musical art", which determines the specificity of manifestation of his/her emotional intelligence and analyzes the scientific views of scientists on the problem of his/her formation. The article shows the problem of formation of professionally significant qualities of a future specialist in the context of the priority directions of education development. There is a short characteristic of emotional intelligence as an individual and personal formation that provides success in the sphere of professional activity. In this article it is emphasized that the specifics of manifestation of emotional intelligence of the professional are caused by features of his professional activity. Features of a lesson of music as a lesson of art are revealed defining peculiar features of a profession "teacher of musical art". Materials and technique of study. The logic and technique of scientific search was provided with observance of initial theoretical positions, approved in science as well as the use of theoretical methods of scientific knowledge: study of scientific literature on a problem of the research, the analysis, synthesis, comparison, generalization, citing that allowed to establish characteristics of a lesson of musical art as the bases for manifestation of emotional intelligence of a teacher-musician and to compare scientific views of scientists on a problem of his/her purposeful formation as a professional and significant quality in the context of modern requirements. The carried-out analysis of scientific views on a problem of formation of emotional intelligence of a future teacher of musical art allowed to allocate the thoughts accented by scientists specifying on: need of the research of the problem of formation of professionally significant, personal qualities of a teacher as a subject of professional activity which spirituality is provided with integration emotional, intellectual, motivational spheres of mentality; universality of emotional intelligence of basic emotional and communicative ability, participating in various spheres of communicative interaction, guaranteeing his/her success; emotional intelligence as a spiritual ability for recognition of emotional mood of others that promotes the best mutual understanding; group of competences of the teacher of musical art (communicativeness, goodwill, figurative thinking, emotionality, self-control, etc.) which affect success of pedagogical activity; empathy as a key component of emotional intelligence; the emotional intelligence as individual and personal education, is subject to effective development by means of musical intoning in the course of the individual and collective occupations. As a result of the theoretical level of the research of the designated problem the peculiar features of manifestation of emotional intelligence of a teacher of musical art caused by features of his/her professional and pedagogical activity are defined in a generalized view. The article shows different scientific views concerning the problem of formation of emotional intellect of a teacher of musical art. The conclusion has been done that the specifics of manifestation of emotional intelligence of a teacher-musician as a component of his professionalism are caused, first, by humanistic essence of a pedagogical profession, and, secondly, by the intonational and sound nature of musical art, its emotional and spiritual dominant. The received knowledge will contribute to structurally functional model of formation of emotional intelligence of a future teacher-musician as his/her individual and personal, professional and significant quality. The emotional intelligence of a teacher of musical art is concretized in such concepts as "experience" in the form of non-verbal knowledge as "a touch and emotional and intellectual birth of thoughts", "figurative thinking", "emotional communication", "self-checking", "self-control" and others. So, theoretical and practical works of scientists on the problem of formation of emotional intelligence of a teacher of musical art make scientific-theoretical bases of the further research of the outlined phenomenon in the direction of development of its structurally functional model of formation as an individual and personal, professional and significant quality of a teacher of musical art.
Keywords: вчитель музичного мистецтва; eacher of musical art; емоційний інтелект; професійно-значуща якість; урок музичного мистецтва; emotional intelligence; professionally significant quality; lesson of musical art